TAVI via alternative access routes: patient selection and 10-year center experience. (14th October 2021) - Rocha, B; Nolasco, T; Teles, R; Madeira, S; Vale, N; Madeira, M; Brito, J; Raposo, L; Goncalves, P; Gabriel, H M; Sousa-Uva, M; Abecasis, M; et al.
Abstract: Background: Femoral access is considered the gold standard for transcatheter aortic valve implantation (TAVI). However, this route might be precluded due to the presence of tortuosity, small vessel diameter and/or peripheral artery disease. We aimed to investigate TAVI through an alternative access (AA), focusing on the selection criteria and clinical outcomes compared to the femoral route (TF). Methods: We conducted an all-comers longitudinal single-centre prospective registry in whom a TAVI was performed. The feasibility, safety and efficacy of TAVI by means of an access route other than standard TF was assessed, according to the VARC-2 criteria. The prospective surgical criteria used at our institution to accept an AA route were: a) TF deemed inappropriate; b) acceptable haemorrhagic risk; c) acceptable general anaesthesia risk; and d) adequate anatomy and diameter within acceptable range (subclavian, axillar, transaortic) or e) age <85 years and non-frail patient (transapical). The primary endpoint was all-cause death at 1-year. Results: From 2008 to 2018, there were 548 patients submitted to TAVI [median age 84 (79–87) years, males 45.4%]. An AA route was used in 100 patients (79 trans-apical, 9 trans-aortic, and 12 trans-subclavian), with a decreasing rate over follow-up (−11% per year). Compared to TF, these patients were younger [80 (77–84) vs. 85 (80–87) years; p<0.001) with a similar baseline surgical risk as per EuroSCORE II [5.1 (3.3–9.0) vs. 4.7 (3.3–7.0); p=0.410). AA patients presented a higher burden of atherosclerotic disease, namely coronary (54.0 vs. 41.3%; p<0.001) and peripheral artery disease (35.0 vs. 16.5%, p<0.001) despite a lower number of other comorbidities (e.g. glomerular filtration rate <50mL/min: 53.1 vs. 64.8%; p=0.030). Left ventricular ejection fraction (56±13 vs 55±12%; p=0.203) and aortic stenosis severity (e.g. valve area: 0.70±0.19 vs. 0.67±0.18cm 2 ; p=0.302) were similar between groups. Haemorrhagic events (minor or major) following TAVI were less often documented in the AA group (11.0 vs 21.7%; p=0.015), contrasting with de novo atrial fibrillation (18.5 vs 7.6%; p=0.048). Overall, 67 patients met the primary endpoint (18.8 vs 16.2%; p=0.584). After adjusted multivariate analysis, the independent predictors of one-year mortality did not include the TAVI access route. Conclusion: In the first 10 years of experience, 1 in every 6 patients was treated with a TAVI by means of an AA, most often trans-apically initially and, nowadays, via a trans-subclavian approach. The use of meticulous prospective selection criteria seems to explain the one-year similar results, regardless of the access route. Funding Acknowledgement: Type of funding sources: None.